Cross-cultural Analysis of Al- Sadat's and Bush's First Inaugural Speeches - Bashir, Ishraga; Hayif, Imad (Advances in Social Sciences Research Journal, 2017)
The present cross-cultural investigation analyzes critically two culturally different inaugural speeches. The researchers have chosen the inaugural speech of the president Bush the son and the inaugural speech of the Syrian president Alasad. It explores the discursive practices of a presumably powerful leaders in two nations/cultures. Drawing upon the theoretical stance of CDA and intercultural pragmatics Theory, the study attempts to examine the contextually-controlled production of the inaugural discourses in the two cultures and the discursive decisions guided by the experts’ ́ context models, being the cognitive interface between discourse and society. The study combines analytic tools from socio-cognitive theory and CDA, in examining (i) the selection of topics and the discursive construction of contextual features, namely setting, participant’s ́ identities, ideology, purposes and (ii) the strategic maneuverings performed revealing of the arguers ́ attempt to maintain balance between the dialectical and the rhetorical goals. The findings from the socio-cognitive study show that the patterns in the discursive practices of each speech indicate ideologically and culturally biased strategies, though they have common points.